Health-Related Habits and Health Promotion Behaviors in People With Alcohol Flushing. (May 2023) - Hwang, In Cheol; Choi, Seulggie
There is limited investigation on health-related behaviors by alcohol flushing. A nationwide cross-sectional study was conducted using data from the Korea Community Health Survey. The final analysis included 130 192 adults with available information on alcohol flushing assessed by a self-reported questionnaire. About a quarter of participants were classified into alcohol flushers. After considering demographics, comorbidities, mental health, and perceived health status, multivariable logistic regression analysis revealed that flushers smoked or drank less and received vaccination or screening more than nonflushers. In conclusion, flushers have healthier behaviors than nonflushers.